2022
DOI: 10.3390/nu14142869
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Effect of Selenium Supplementation on Production of Selected Cytokines in Women with Hashimoto’s Thyroiditis

Abstract: The impact of selenium on the course of Hashimoto’s thyroiditis (HT) was mainly assessed by monitoring the titer of antithyroid autoantibodies in most of the studies conducted hitherto. On the other hand, the imbalance in activity of T cells such as Th1, Th2, Th17, and Treg may be relevant in the pathogenesis of this disease. Hence, the assessment of changes in the secretion of cytokines by these cells during selenium supplementation in patients with HT seems to be an important issue and was the main goal of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…Thus, selenium supplementation seems to upregulate activated T cells ( 44 ) and to inhibit the release of several pro-inflammatory cytokines, including interleukin 2, interferon gamma (IFNγ), and tumor necrosis factor ( 2 , 45 ). A recent study found that 100 μg daily selenium supplementation in 29 women with AIT reduced IFNγ and increased interleukin 1β concentrations ( 46 ). Although the present trial found no positive effects on clinical outcomes, such as QoL and the LT4 dosage, further research is needed to explore whether the potential effects of selenium on the immune system, the oxidative stress burden, and low-grade inflammation are of clinical significance in patients with thyroid diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, selenium supplementation seems to upregulate activated T cells ( 44 ) and to inhibit the release of several pro-inflammatory cytokines, including interleukin 2, interferon gamma (IFNγ), and tumor necrosis factor ( 2 , 45 ). A recent study found that 100 μg daily selenium supplementation in 29 women with AIT reduced IFNγ and increased interleukin 1β concentrations ( 46 ). Although the present trial found no positive effects on clinical outcomes, such as QoL and the LT4 dosage, further research is needed to explore whether the potential effects of selenium on the immune system, the oxidative stress burden, and low-grade inflammation are of clinical significance in patients with thyroid diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Selenium deficiency may upregulate Th1/Th2 effector molecules and enhance immune responses. Daily supplementation of 100 μg of Selenium has been shown to improve thyroid function and quality of life in patients by reducing interferon-γ levels and increasing interleukin-1β levels ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…Se deficiency may upregulate Th1/Th2 effectors and enhances immune responses. The possible therapeutic effect of Se in HT to improve immune function was validated in a prospective study conducted in 2022, which showed that Se supplementation with 100ug per day improved thyroid function and the quality of life of patients by decreasing interferon gamma concentrations and increasing interleukin 1b concentrations (46).…”
Section: Se and Hashimoto's Thyroiditismentioning
confidence: 99%